Adaptive Sliding Mode Control of PMLSM Drive - Maamar Yahiaoui; Abderrahmane Kechich; Ismail Khalil Bouserhane (Institute of Advanced Engineering and Science, 2017)
In this paper, we propose a study by software MATLAB/Simulink of the adaptive nonlinear controller of permanent magnet linear synchronous machine. The lumped uncertainties due for saturation magnetic and temperature and distribution load effects in performances of the system control. To resolve this problem the sliding mode controller is designed with estimator of load force by MRAS method the simulation results prove clearly the robustness of controlling law and estimator method.